From economic difficulties to psychological maladjustment in Italian women during the Covid-19 pandemic: does marital dissatisfaction moderate or mediate this association? - Camisasca, Elena; Covelli, Venusia; Cafagna, Dario; Manzoni, Gian Mauro; Cantoia, Manuela; Bavagnoli, Alessandra; Crescenzo, Pietro; Marsicovetere, Vincenzo; Pesce, Mario; Visco, Marina Angela (Frontiers in Psychology, 2023)
The empirical study about the impact of economic difficulties due to Covid-19 on the psychological maladjustment of Italian women by considering perceived stress and marital satisfaction is an area worthy of investigation. The study explored these variables by hypothesizing that marital satisfaction (DAS) could moderate or mediate the links between economic difficulties, perceived stress (PSS), and psychological maladjustment (PGWBI). Participants were 320 women, and 39.7% of them said that the Covid19 significantly impacted their family income. Results indicated that marital satisfaction did not moderate the associations investigated. Conversely, data showed how economic difficulties (X) predicted lower psychological maladjustment through the mediation of perceived Stress (M1), which, in turn, was associated with higher levels of marital dissatisfaction (M2). Results are discussed in terms of research implications. .